PENGARUH PERUBAHAN TATA GUNA LAHAN TERHADAP NILAI CURVE NUMBER PADA DAS SAROKAH - Zainah, Nor; Maulana, Mahendra Andiek; Margini, Nastasia Festy (Fakultas Teknik, Universitas Wiraraja, 2024)
Changes in land use in a watershed can significantly affect its hydrological characteristics. In addition to extreme rainfall events, land-use changes are among the factors contributing to flooding. This study aimed to determine changes in CN values due to land use changes in the Sarokah Watershed. Land use analysis was conducted by training objects on satellite image data acquired by Landsat 7, Landsat 8, and Sentinel 2A. From 2002 to 2013, there was a 9.03% decrease in the area of paddy fields and a 5.83% increase in the area of farms in the Sarokah Watershed. From 2013 to 2023, there was a 3.16% increase in built-up area and a 5.26% decrease in the area of paddy fields. According to the district's spatial plan, from 2023 to 2042, there will be a 29.15% increase in the built-up area and a 19.69% increase in the area of paddy fields. However, forest/tree areas and farm areas will decrease by 17.36% and 23.96%, respectively. Based on the 2023-2043 land use changes, the highest increases in CN values in 2043 will be in Sub-watersheds S15, S6, and S14 at 16.5%, 13.2%, and 10.8%, respectively.